Modelling of seat belt use intention for intercity buses based on health belief model. Issue 2 (2nd January 2019) - Nambulee, Watanya; Jomnonkwao, Sajjakaj; Siridhara, Siradol; Ratanavaraha, Vatanavongs
ABSTRACT: The increasing severity and number of intercity bus accident occurrences result in huge loss of lives and assets. However, we can reduce these risks and the severity by wearing seat belts while travelling in buses. This study aims to determine the factors that affect the seat belt use behavioural intention of intercity bus passengers. These factors could be considered for policy plans are proposed to the government for promoting more seat belt use, divided into teenager and adult groups, by applying of health belief model (HBM). The results of the study show that the two models were different. Every factor of the two groups influenced the seat belt use behavioural intention. Perceived severity had the most significant positive influence on the seat belt use behavioural intention in the teenager group, while perceived benefits had the most significant positive influence in the adult group. Perceived barriers had the most significant negative influence in both groups.